ANALISIS PENGARUH RASIO PROFITABILITAS, LIKUIDITAS, LEVERAGE, EPS, DAN SIZE TERHADAP RETURN SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (2011-2013) (Students' Journal of Accounting and Banking, 2015)
This study aims to determine the effect of profitability ratio (ROA), liquidity (LDR), leverage (DER), EPS, and Size to return stock banking companies listed in the Indonesia Stock Exchange (BEI) 2011-2013. The population in this study are all banking companies listed in the Indonesia Stock Exchange (BEI) 2011-2013. Determination sempel by using purposive sampling. The sample in this study as many as 32 banks that meet the criteria. Methods of data collection in the form of technical documentation and multiple regression analysis as an analytical technique. These results indicate that profitability represented (ROA), liquidity represented (LDR), Leverage(DER), EPS and Size simultaneously significant effect on stock returns. Based on the partial test represented profitability (ROA) significant positive effect on stock returns. While liquidity represented (LDR), Leverage (DER), EPS and Size is no significant effect on stock returns.Keywords: Profitability (ROA), Liquidity (LDR), Leverage (DER), EPS Size, Stock Returns